Secondary-Level Study of Accounting and Subsequent Performance in the First College Course. - Rosen, L. S.; Baldwin, Bruce A.; Howe, Keith R. (The Accounting Review, 1982)
ABSTRACT: This paper compares students who studied accounting in high school (Group I) to those students who did not (Group II). Two questions were addressed. First, do Group I students outperform Group II students in the first college-level accounting course? Second, what impact does prior accounting education have on dropout behavior from the first college-level course? Data were compiled for 498 students enrolled in elementary financial accounting. The first question was addressed by performing an analysis of covariance with repeated measures on examination scores. Vocabulary and quantitative skills scores were used as the covariates. The second question was evaluated by analysis of total drop-outs and drop-out patterns. Overall, Group I students performed no differently on examinations than those in Group II. While they scored higher on early examinations, they scored less well later. There was no difference in drop-out rate, although Group I students tended to drop later in the semester.